Commodifying Mental Health: Genre and Commercial Strategy in Sinemaku Pictures’ Film Narratives - Nur Endah, Dian (Foremost Journal, 2025)
This study examines how mental health operates as both an emotional narrative device and a commercial strategy in three Indonesian films: Kukira Kau Rumah (2021), Ketika Berhenti di Sini(2023), and Bolehkah Sekali Saja Kumenangis (2024). Intrinsically, the films portray young female protagonists entangled in familial dysfunction and psychological distress, reinforcing popular genre formulas of emotional victimhood and romantic salvation. Drawing on Cawelti’s formula theory and Adorno’s culture industry critique, the study shows how mental health is stylized into consumable spectacle, balancing originality with familiar tropes to ensure audience identification. Extrinsically, the commodification of mental health is evident in promotional strategies using emotional endorsements, celebrity influence, and outreach programs. Through the lens of Hesmondhalgh’s political economy of media and Dyer’s star studies, the research argues that mental health becomes emotional capital—marketed through star personas and affective narratives to boost engagement, empathy, and commercial success.